Mechanics of heel-strike plantigrady in African apes. Issue 145 (August 2020) - Zeininger, Angel; Schmitt, Daniel; Wunderlich, Roshna E.
Abstract: The initiation of a walking step with a heel strike is a defining characteristic of humans and great apes but is rarely found in other mammals. Despite the considerable importance of heel strike to an understanding of human locomotor evolution, no one has explicitly tested the fundamental mechanical question of why great apes use a heel strike. In this report, we test two hypotheses (1) that heel strike is a function of hip protraction and/or knee extension and (2) that short-legged apes with a midfoot that dorsiflexes at heel lift and long digits for whom digitigrady is not an option use heel-strike plantigrady. This strategy increases hip translation while potentially moderating the cost of redirecting the center of mass ('collisional costs') during stance via rollover along the full foot from the heel to toes. We quantified hind limb kinematics and relative hip translation in ten species of primates, including lemurs, terrestrial and arboreal monkeys, chimpanzees, and gorillas. Chimpanzees and gorillas walked with relatively extended knees but only with moderately protracted hips or hind limbs, partially rejecting the first hypothesis. Nonetheless, chimpanzees attained relative hip translations comparable with those of digitigrade primates. Heel-strike plantigrady may be a natural result of a need for increased hip translations when forelimbs are relatively long and digitigrady is morphologically restricted. In addition, foot rollover from the heel to toe in large, short-legged apes may reduce energetic costs of redirecting the center of mass at the step-to-step transition as it appears to do in humans. Heel strike appears to have been an important mechanism for increasing hip translation, and possibly reducing energetic costs, in early hominins and was fundamental to the evolution of the modern human foot and human bipedalism. Highlights: The evolution of heel strike in great apes and humans is poorly understood. We test the function of heel strike and foot rollover in chimpanzees and gorillas. Heel strike increases effective limb length in relatively short-legged African apes with long grasping toes. Foot rollover and hip protraction increase stride length and may reduce energy costs. These results add to our understanding of the evolution of the human foot.